Analysis of Net Profit and Cash Flow to Share Price Through Auditor Quality - Reva Maria Valianti; Rismansyah Rismansyah; Adie Kurbani (Integrated Journal of Business and Economics (IJBE), 2021)
The design of this research Net profit in financial statements is one of the company's performances to get more value from investors. Net profit is also one of the tools to measure the income and costs of a company. cash flow statements aim to report both inflows and cash outflows. The cash flow statement also provides information on receipts and payments during a given period, the variable cash flows used, namely cash flow from operating activities, cash flows from investment activities and cash flows from financing activities. Share price is fickle or fluctuating all the time.  In order to be trusted by the wearer or investor, it is necessary for auditors to bridge the needs of report users and financial report providers. The role of auditors is very important in bridging between the interests of investors and the interests of the company as a user and provider of financial statements. Research methods used in this the findings in this study are known that each variable X has a direct and significant effect on variables Y and Z. Variable Z is the quality of auditors in this study is not an intervening variable or mediator in the relationship X to Y.